2018
DOI: 10.1016/j.ijsu.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a colorectal enhanced recovery program implementation on clinical outcomes and institutional costs: A prospective cohort study with retrospective control

Abstract: Implementing a colorectal enhanced recovery program is feasible, efficient for functional recovery and hospital stay reduction, safe, and cost-effective. High patient satisfaction and nursing workload reduction may also be expected, but high protocol adherence is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…There was an average 1458 Euros ($1655 USD) saved per colorectal surgery case when ERAS was performed. 18 Other institutions have shown ERAS spine surgery LOS was decreased by 1.5 to 2 days with no change in complication or readmission rate. The estimated potential cost savings from that study was $2.4 million.…”
Section: Discussionmentioning
confidence: 94%
“…There was an average 1458 Euros ($1655 USD) saved per colorectal surgery case when ERAS was performed. 18 Other institutions have shown ERAS spine surgery LOS was decreased by 1.5 to 2 days with no change in complication or readmission rate. The estimated potential cost savings from that study was $2.4 million.…”
Section: Discussionmentioning
confidence: 94%
“…From a nancial perspective, in this study, the ERAS Program reduced direct costs per patient. Several studies have shown that ERAS protocols were cost-effective (20,21,22). These cost studies also con rmed a decrease LOS in their cohorts.…”
Section: Discussionmentioning
confidence: 86%
“…Certainly, perioperative care may well affect functional outcomes, post-operative length of hospital stay and morbidity. 26,27 In this study, however, similar evidence-based principles of perioperative care were implemented by a multidisciplinary group to enhance post-operative recovery at both institutions.…”
Section: Discussionmentioning
confidence: 99%